The independence of local authorities on the problem of governance of the state - pearnpitak, kittipong Pearnpitak (King Prajadhipok’s Institute Journal, 2021)
The objective of this study was to reflect 1) the problems of local Administrative organization in regard to the local financial without autonomy for fair resource allocation and decentralization from the central government committed with a high proportion of intergovernmental transfer. These conditions have led to encounters with domination by the structures of political power, which were changed from familiarity to unfamiliarity in a local division. In the same way, the law always left room for using loopholes as tools for distorting the truth in light of benefits through purposes of democratic essence. This situations has caused inequality in processes of public resource allocation for a long time. These problems could be addressed by reforming Local Financial from the base of development. It should focus on increasing the competency of people as citizens, who could understand their roles, duties, and responsibilities for supporting structures of local democracy for sustainability.